Peter Pan Syndrome "Men Who Don't Grow": Developing a Scale. (June 2021) - Kalkan, Melek; Batık, Meryem Vural; Kaya, Leyla; Turan, Merve
Peter Pan Syndrome is a concept that used to characterize the "never-growing" men who have reached an adult age, but cannot face their adult sensations and responsibilities. Individuals with Peter Pan Syndrome have difficulties in social and professional relationships because of their irresponsible behaviors and narcissistic properties. The purpose of this study is to develop a scale in order to measure the level of Peter Pen Syndrome in male individuals. In accordance with this purpose, the draft form was sent to experts to get their feedback, and some statements have been revised in accordance with the feedback. The Peter Pan Syndrome Scale is a twenty-two-item self-report measurement, and each item is evaluated on five-point Likert Type scale. Construct validity of the scale was determined by exploratory factor analysis (EFA) and a three-factor model was created, namely, "Escape from Responsibility", "Power Perception, " and "Never Growing Child". EFA results shows that these three factors were describing 47.05% of the variance. Results of EFA were verified by confirmatory factor analysis (CFA). The internal consistency coefficient and the confidence coefficient of the split-half were used to determine the reliability of the scale. The Cronbach's alpha value was found to be 0.88 for the total scale.